Radiation Therapy in Management of Sporadic and Neurofibromatosis Type 1-Associated Malignant Peripheral Nerve Sheath Tumors - Kahn, Jenna; Gillespie, Andy; Tsokos, Maria; Ondos, John; Dombi, Eva; Camphausen, Kevin; Widemann, Brigitte C.; Kaushal, Aradhana (Frontiers in Oncology, 2014)
Introduction: Malignant peripheral nerve sheath tumors (MPNST) are highly aggressive soft tissue sarcomas in which complete surgical resection is the mainstay of therapy. However, the recurrence rate is high and few options remain for refractory or metastatic MPNST. This study examines the outcomes of adjuvant radiation therapy in MPNST in patients with and without neurofibromatosis-1 (NF1) and reviews the literature on use of radiation for MPNST. Methods: A retrospective review of 33 MPNST patients between 1990 and 2012 evaluated at the NIH. All diagnoses were pathologically confirmed at the NCI. Clinical presentation, treatment, and survival were analyzed. Results: Thirty-three patients were included, 18 NF1-associated, 15 sporadic tumors. Tumor location included extremity (58%), trunk (36%), and head/neck (6%). Histologic grade showed 25 high grade tumors compared to 7 low grade tumors. Twenty patients were treated with radiation therapy, (median total dose of 58.5 Gy with 1.8 Gy/fraction). A median survival of all patients was 46.5 months and 43.7% overall 5 year survival. Prognostic factors include extent of resection, tumor location, and histology grade. Radiation was not found to be a prognostic factor for overall survival. Conclusions: This study is consistent with previous studies regarding the role of radiation in the management of MPNST. Prospective evaluation of adjuvant radiation will allow to more fully define the role of radiation in MPNST.